Penyebab Miskonsepsi Siswa Kelas 9 pada Materi Pecahan Bentuk Aljabar Berdasarkan Teori Konstruktivisme - Djadir; Nurdin Arsyad; Melda Datu Kalu (Issues in Mathematics Education (IMED), 2021)
This study aims to determine the factors that cause student misconceptions form 9th grade on algebraic form fraction in terms of the principles of constructivism learning theory. This type of research is qualitative research using a descriptive approach. The subjects in this study were 5 grade 9 students who experienced the most misconceptions with the lowest scores. The instrument used in this study was a student misconception diagnostic test consisting of several descriptive items accompanied by Certainty of Response Index (CRI) and an interview guide. The principles of constructivism learning theory referred to in this study are the learning environment, students' initial knowledge, student abilities, student activeness in learning and student learning experiences. The results showed that the misconception was caused by several factors, both internal and external, in terms of the principles of constructivism theory.